AIR EXTRACTION SYSTEMS FOR ICE CORE AND CO_2 AND CH_4 CONCENTRATIONS IN THE PAST ATMOSPHERE - ナカザワ, タカキヨ; マチダ, トシノブ; エスミ, ケンジ; タナカ, マサユキ; フジイ, ヨシユキ; アオキ, シュンジ; ワタナベ, オキツグ; NAKAZAWA, Takakiyo; MACHIDA, Toshinobu; ESUMI, Kenji; TANAKA, Masayuki; FUJII, Yoshiyuki; et al. (National Institute of Polar Research, 1992)
P(論文) Dry and melt extraction systems have been developed to determine respectively the CO_2 and CH_4 concentrations of ancient air trapped in the polar ice core. The day extraction system was confirmed to be capable of crushing a core sample of 1kg to fine powder within 2 min, and its air extraction efficiency was estimated to be 98%. The air for the CH_4 measurements was extracted by melting core samples in an evacuated chamber. The CO_2 and CH_4 concentrations were determined using gas chromatography. The overall precision of our analyses is better than ±1 ppmv for CO_2 and ±10 ppbv for CH_4. Two Antarctic ice cores were used in this study. The ice core drilled at Mizuho Station (70°42'S, 44°20'E) showed that pre-industrial levels of the CO_2 and CH_4 concentrations (3300-200 yrs BP) were 279-287 ppmv and 690-750 ppbv, respectively and both concentrations increased rapidly for the last 200 years. It was also found that the CO_2 concentrations between 800 and 200 yrs BP were higher by almost 7 ppmv than those in remaining pre-industrial time, due probably to CO_2 release from the oceans and/or the biosphere. The Yamato core drilled near the end of ice flow (near the Yamato Mountains) showed concentrations of 230-240 ppmv and 530-580 ppbv for CO_2 and CH_4,respectively, which are apparently lower than post-glacial background levels, implying that the core was formed in the glacial period. departmental bulletin paper